Survival Analysis of Clinicopathology Profile and Risk Factor in Cervical Cancer with Surgery - Ainun Ganisia, Yahya Irwanto, Diadjeng Setya Wardani, Karmanis, Ineke Permatasari, Aliesya Patricia, Aswin Rafif Khairullah, Ristaqul Husna Belgania, Karjono, (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Cervical cancer is one of the most preventable types of cancer compared to all cancer cases , but it is also deadly. Objective: This study aimed to determine the five year survival rate of surgical cervical cancer at Saiful Anwar Hospital Malang and to know the effect of clinicopathological profile and risk factors on survival rate. Methods: Our method is analytic observational with a retrospective cohort type using medical records of surgical cancer cervix from January until December 2017. The analysis used the Log-rank test, Kaplan Meier, and Cox regression. Results: The total of the 144 study samples, found 92 alive and 52 dead. This research of clinicophatology profile showed significant affect in stage (p .001), histopathology (p .006), degree of differentiation (p .000), and lymph node metastases (p .000). While the research of risk factor showed significant affect in age (p- value 0.000), total of parity (p .000), marital history (p .000), occupation (p .003), menstrual history (p .003), and type of contraception (p 0.000), type of therapy (p .001). And then, it was found no significant affect in BMI (p .471) area of residence (p .475). Conclusion:. The survival rate of cervical cancer patients in five years with surgery is 90 %. Based on the clinicopathological profile, it was found that that stage variable, histopathology, degree of differentiation, and lymph node metastases significantly affect the survival rate. In the characteristics of risk factors, The variables of age, parity, marital history, occupation, menstrual history, contraception, type of therapy, and place of residence) have a significant effect on survival.